Influence of Electron-Poor Conjugated Polymers on the Selective Dispersion of Carbon Nanotubes - Cruikshank, Jack (My University, 2022)
The unique thermal, electronic, and optical properties of single-walled carbon nanotubes (SWNTs) can be used in a variety of applications. However, all currently available production methods result in a heterogenous mixture of semiconducting and metallic species. SWNTs also self-aggregate, resulting in minimal solubility in solvents, preventing their immediate incorporation into many applications. These challenges have resulted in the development of various purification methods, but the use of conjugated polymers is considered to be the most scalable technique. Currently, conjugated polymers have allowed for the complete isolation of semiconducting SWNTs using electron-rich conjugated polymers such as polythiophenes, polycarbazoles, and polyfluorenes. Conversely, the isolation of pure metallic SWNTs still requires improvement. Recently, a two-polymer system was developed for the enrichment of metallic SWNTs using an electron-rich conjugated polymer to remove semiconducting SWNTs, followed by an electron-poor polymer to disperse the remaining metallic SWNTs. This technique represented a significant step forward in the enrichment of metallic SWNT samples using conjugated polymers, but refinement is still possible. The aim of this thesis is to improve this scalable technique for the enrichment of metallic SWNTs. Specially, two reactions on poly(fluorene-co-pyridine) were investigated in an effort to generate a more electron deficient polymer backbone. The first reaction involved the addition of a dinitrobenzene moiety by means of the Zincke reaction. It was found that the functionalization of the polymer backbone using the Zincke reaction was not feasible, likely due to steric hinderance. Research efforts were then redirected to a reaction involving the addition of a less bulky trifluoroacetyl group by reaction of the polymer with trifluoroacetic anhydride. This investigation led to the straightforward and complete functionalization of the polymer backbone producing acetylated poly(fluorene-co-pyridine). Next, the ideal dispersion conditions were tuned for the acetylated poly(fluorene-co¬-pyridine) to be incorporated into the two-polymer extraction system. This novel polymer showed higher dispersion concentration and improved selectivity toward metallic SWNTs than previously developed. Characterization of the polymer-SWNT dispersions were conducted using UV-vis-NIR spectroscopy, and conductivity techniques to evaluate their electronic purity.